The use of botulinum toxin (BoNT) in urology - review - Szwed, Jakub; Szwed, Monika; Szwed, Weronika; Miga, Nadia (Journal of Education, Health and Sport, 2022)
Introduction and purpose Botulinum neurotoxin (BoNT) prevents the release of acetylcholine into the synaptic cleft of the neuromuscular junction, which causes flaccid muscle paralysis. A non-obvious specialization that uses botulinum toxin is urology. The aim of this article is to present a literature review regarding the use of botulinum toxin in the treatment of urological diseases. Description of the state of knowledge In the overactive bladder syndrome, with resistance to oral medications, an alternative is botox injections into the bladder wall, which reduce the intensity of urgency and pollakiuria. Treatment of BPH with botulinum toxin injection may be an alternative to surgical and pharmacological treatment. Intra-articular botox injection causes smooth muscle relaxation and gland atrophy through prostate tissue apoptosis. Clinical studies show promising therapeutic effects of using Botox injections in the treatment of intramural cystitis. It reduces the feeling of bladder pain and the worsening of other symptoms. Panunzio et al. Presented a meta-analysis of prospective studies that showed a statistically significant improvement in pain perception after injection of botulinum toxin into the pelvic structures, compared with baseline values ​​for CPPS, in all cohorts evaluated. Summary Urology uses the entire spectrum of botox possibilities, from myocrelation in the bladder hyperresponsiveness syndrome, through neuromodulation and apoptosis induction in benign prostatic hyperplasia, ending with anti-inflammatory and analgesic properties in bladder pain syndrome and chronic pelvic pain syndrome.